Penerapan Aplikasi Mefuko (MMSE Untuk Fungsi Kognitif) Pada Lansia Dengan Demensia - Novita Wulan Sari; Margiyati Margiyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
An elderly person is someone who has reached the age of 60 years and over. One of the health problems that often occurs in the elderly is a decline in memory, learning and cognitive abilities in the elderly which causes them to have difficulty interacting and being difficult to understand. Conditions that affect cognitive abilities in the elderly are called dementia. Dementia is a chronic and progressive decline in memory and thinking function, causing disruption of functional activities. Nursing interventions that can be given to the elderly to improve cognitive function in the occurrence of dementia include brain gymnastics. The case study design used is descriptive research. The method used to collect data is using the Android-based MMSE (Mini Mental State Examination), namely MEFuKo (MMSE for Cognitive Function) to determine the level of dementia in the elderly. Brain exercise therapy (brain gym) is carried out for 7 consecutive days, 1 meeting per day with a duration of 15 minutes. Subject I's MMSE score before brain exercise therapy was 16 (presence of definite cognitive impairment) increased to 19 (presence of probable cognitive impairment) and there was an increase of 3 in total MMSE scores. The MMSE score in subject II before brain exercise therapy was 19 (possible cognitive impairment), after therapy the MMSE score became 23 (probable cognitive impairment) and there was an increase of 4 in total MMSE scores. The more activities you do, the less likely it is that seniors will experience a decline in cognitive function. The conclusion is that there was an increase in cognitive function in the two case study subjects which illustrate the application of brain gym therapy to cognitive function in elderly people with dementia. Brain exercise therapy is recommended to improve working memory function which can improve the quality of life of the elderly.